1975
DOI: 10.1577/1548-8659(1975)104<726:agafoy>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Age, Growth, and Fecundity of Yellow Perch, Perca flavescens, in Lake Michigan near Ludington, Michigan

Abstract: Yellow perch were studied as a portion of a total environmental baseline study in 1972 before operation of a new pumped storage power plant on the eastern shore of Lake Michigan near Ludington. Of 1,546 perch taken by gill nets, age III (1969 year class) and IV fish contributed 40.1% and 27.4% of the total number, with male fish being taken much more frequently than females in all age classes during spring sampling. Comparative growth and lengthweight data indicated that the perch were generally growing to lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

1977
1977
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 0 publications
1
18
1
Order By: Relevance
“…Rapid growth sometimes allows female yellow perch to become sexually mature at age two (Herman et al, 1964;Brazo et al, 1975;Headley and Lauer, 2008). SSB was calculated based on abundance by length categories of females at the start of the year (reproduction is in spring before growth or substantial mortality), mass-at-length, and the proportion mature at length (Eq.…”
Section: Growth Size Composition Maturity and Biomass Calculationsmentioning
confidence: 99%
“…Rapid growth sometimes allows female yellow perch to become sexually mature at age two (Herman et al, 1964;Brazo et al, 1975;Headley and Lauer, 2008). SSB was calculated based on abundance by length categories of females at the start of the year (reproduction is in spring before growth or substantial mortality), mass-at-length, and the proportion mature at length (Eq.…”
Section: Growth Size Composition Maturity and Biomass Calculationsmentioning
confidence: 99%
“…(Pearse, 1925;Eddy & Surber, 1960;Muncy, 1962 1972) but the fecundity of Eurasian perch has been more frequently studied (Huitfeld-Kaas, 19 16;Syrovatskaya, 1927;Dryagin, 1948;Konovalova, 1955;Zakharova, 1955;Krasikova, 1958;Shilenkova, 1959;Pihu, 1964;Stehlik, 1968). Fecundity of perch in the Deeside lochs falls within the range reported for yellow perch (3035-109 000) and of Eurasian perch (950-2 10 000) and values are similar to those quoted for absolute fecundity and relative fecundity for most perch populations by Thorpe (19774. Fecundity varies greatly between perch populations (Thorpe, 1977b) and also varies within populations (EvtyukhovaRekstin, 1962;Popova, 1965;Sheri & Power, 1969;Tsai & Gibson, 197 1 ;Brazo et al, 1975). Thorpe (1977b) considered that the variation in a single habitat suggests that differences in food-supply, spawning conditions and degree of exposure to the wind may be responsible.…”
Section: Fecunditymentioning
confidence: 99%
“…Previous studies of yellow perch SSD have found small to large differences in total length between genders of the same age (Brazo et al 1975;Ridgway and Chapleau 1994;Scholten et al 2001;Headley and Lauer 2008;Schoenebeck and Brown 2012). However, these studies were performed over a small spatial scale so that the prevalence of SSD in yellow perch over a larger geographic area remains unknown.…”
Section: Introductionmentioning
confidence: 98%